Effect of Acupuncture for Mixed Urinary Incontinence in Women: A Systematic Review - Long, Zilin; Chen, Huan; Yu, Shudan; Wang, Xinlu; Liu, Zhishun (Frontiers in Public Health, 2022)
Background: mixed urinary incontinence increasingly undermines women's quality of life. Previous studies showed some effects of acupuncture for MUI, but no systematic review has been done to evaluate the efficacy andsafety of acupuncture for MUI in women. Objective : to systematically review the efficacy and safety of acupuncture forwomen with MUI. Methods: ten databases (i.e. PubMed, Web of Science, Embase, ClinicalTrials.gov,the Cochrane Library, CBM, Scoups, CNKI, VIP and WANFANG DATA) were searched up to 19 th July 2021, using tailored search strategies withkeywords not limited to "female", "mixed urinary incontinence", "acupuncture", and "randomized controlled trial", etc. RCTsand quasi-RCTs were included if investigating effect of any type of acupuncture for female patients with MUI. Data were extracted from eligible studies, and risks of bias were assessed accordingto the CochraneHandbook from seven aspects using the RevMan 5.4 software. Results: A totalof three randomized studies with591 women were included. The risk of bias among the studies varied, with majorconcernson blinding of participants and outcome assessor. Liu’s study (497) mainly showed that electroacupuncture’s effect on reductionof numbers of incontinence, urgency, nocturia episodes, and amount of urine leakage etc was not inferior to that of PFMT-Solifenacin group at 12, 24 and 36 weeks. Zhan’s study (60) showed that electroacupuncture reduced significantly more amount of urine leakage than Tolterodine at 8 weeks, with no data on incontinence episodes frequency. All 3 studies reported that acupuncture significantly increased the quality of life assessed by ICIQ score. In addition, incidence of acupuncture-related adverse events was rare, while antimuscarinic agents related adverse events were common in two studies. Conclusion: Although acupuncture showed some benefitfor women with MUI, more evidences were required to draw a solid conclusion of effectiveness and safetyof acupuncture for women with MUI.